단일 3차 의료기관에 내원한 당뇨병성 족부병변 환자의 창상 배양검사를 통한 세균 검출 현황 - 정성윤; 이명진; 이승엽; 이상윤; Jung, Sung Yoon; Lee, Myoung Jin; Lee, Seung Yup; Lee, Sang Yoon (대한족부족관절학회지, 2021)
Purpose: The present study aimed to develop guidelines regarding initial choice of antibiotics for diabetic foot ulcers (DFU) by investigating bacterial isolates. Materials and Methods: This study included 223 DFU patients that visited a single tertiary hospital and underwent bacterial culture between January 2016 and February 2020. The study was conducted in two parts: 1) to compare bacterial isolates and wound healing according to comorbidities such as chronic kidney disease (CKD) and peripheral artery disease (PAD), and 2) to compare bacterial isolates according to wound depth using the Wagner classification. Results: Of the 223 patients, 43 had CKD (group A), 56 had PAD (group B), 30 had CKD and PAD (group C), and 94 had none of these comorbidities (group D). The isolation rate for multidrug-resistant gram-negative bacteria (MRGNB) and gram-negative to gram-positive bacteria ratio were highest in group C (p=0.018, p=0.038), and the proportion that achieved wound healing was lowest in group C (p<0.001). In the second part of the study, subjects were classified into 5 grades by wound depth using the Wagner classification; 13 grade I, 62 grade II, 60 grade III, 70 grade IV, and 17 grade V. No significant difference was observed between these grades in terms of isolation rates or gram-negative to gram-positive bacteria ratios. Conclusion: This study suggests antibiotics that cover gram-negative bacteria including MRGNB produces better results in the presence of CKD and PAD and that initial antibiotic choice should be based on the presence of CKD and PAD rather than wound depth.